2022
DOI: 10.3389/fendo.2022.938500
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cumulative live birth rate and perinatal outcomes in young patients with low anti-müllerian hormone levels using two ovulation promotion protocols: A cohort study

Abstract: ObjectiveTo compare cumulative live birth rates and perinatal outcomes of young IVF/ICSI patients with low anti-Mullerian hormone (AMH) levels on a gonadotropin-releasing hormone antagonist (GnRH-ant) regimen with those on a high progesterone state of ovulation (PPOS) regimen.MethodsWe retrospectively analyzed 798 patients who underwent in vitro fertilization (IVF) or intracytoplasmic sperm microinjection (ICSI) between January 2015 and December 2020 at the Third Affiliated Hospital of Zhengzhou University. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In women with PCOS, LH levels ranged from 1.62 to 2.52 IU/L ( 40 43 ), while in infertile women with normal ovarian reserve, LH levels were between 1.56 and 3.54 IU/L ( 12 , 14 , 44 46 ). Poor responders showed LH levels in the range of 2.4 to 5.55 IU/L ( 6 , 47 49 ). Moreover, research indicated that the LH level at the hCG trigger was 3.68 ± 2.69 IU/L for patients younger than 35 years and 4.77 ± 3.10 IU/L for patients older than 35 years ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In women with PCOS, LH levels ranged from 1.62 to 2.52 IU/L ( 40 43 ), while in infertile women with normal ovarian reserve, LH levels were between 1.56 and 3.54 IU/L ( 12 , 14 , 44 46 ). Poor responders showed LH levels in the range of 2.4 to 5.55 IU/L ( 6 , 47 49 ). Moreover, research indicated that the LH level at the hCG trigger was 3.68 ± 2.69 IU/L for patients younger than 35 years and 4.77 ± 3.10 IU/L for patients older than 35 years ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…A tailored ovarian stimulation regimen was designed, taking into account each patient’s age, body mass index (BMI), and ovarian reserve. Specifically, for women with DOR, milder stimulation protocols and GnRH-ant protocols were more commonly used ( 22 ). Regardless of the protocol employed, routine monitoring of serum hormone levels, such as luteinizing hormone (LH), estradiol (E2), and progesterone (P), was conducted during the stimulation process.…”
Section: Methodsmentioning
confidence: 99%
“…It is one of the hormones used to measure the ovarian reserve or the number of eggs remaining in the ovaries. , Serum levels of AMH can be used to predict the response to fertility treatments and can be used to diagnose conditions such as polycystic ovary syndrome (PCOS) and POI . Low levels of AMH indicate poor ovarian reserve and a high risk of poor outcomes from fertility treatments . High levels of AMH can indicate PCOS, where the ovaries produce excess hormones and produce cysts on the ovaries .…”
Section: Introductionmentioning
confidence: 99%
“…37 Low levels of AMH indicate poor ovarian reserve and a high risk of poor outcomes from fertility treatments. 38 High levels of AMH can indicate PCOS, where the ovaries produce excess hormones and produce cysts on the ovaries. 39 In fact, the previous studies have shown that the combination of FSH, LH, PRL, and AMH is more informative than the assessment of each hormone alone.…”
Section: ■ Introductionmentioning
confidence: 99%